PLEOMORPHIC ADENOMA PRESENTING AS A PERITONSILLAR SWELLING: A RARE PRESENTATION - Jovanović, Anđelina (Medical Research, 2023)
Pleomorphic adenoma, which is considered to be the most common benign neoplasm of the small salivary glands, occurs mainly in the region of the hard palate with mild predilection for women and the peak incidence between the third and sixth decades of life. We present the case of a fifty-one-year-old patient with a left peritonsillar region tumor that the patient has known about for several years. Clinical and radiological examination (computed tomography) indicated a clearly limited, encapsulated tumor change in the left peritonsillar region, 2.5 x 2.5 cm in diameter. The change was completely surgically removed transorally and pathohistologically verified as a pleomorphic adenoma of the small salivary gland. Computed tomography and correct pathohistological diagnosis are essential for the decision on surgical treatment in order to completely remove the lesion. Although it is a benign tumor, early detection is necessary due to adequate surgical treatment. Complete excision of the tumor is necessary to prevent regrowth and possible malignant transformation.
Keywords: pleomorphic adenoma, asymptomatic tumor, peritonsillar swelling